Investment-Specific Productivity Growth : Chile in a Global Perspective - Di Bella, Gabriel (IMF Working Papers; Working Paper ;, 2009)
By the end of 2007, Chile's total factor productivity was lower than ten years earlier, a performance that contrasted sharply with the previous decade, when productivity grew by a cumulative 30 percent. This paper assesses productivity trends in Chile, by decomposing productivity into investment-specific technological change (associated with improvements in the quality of capital) and neutral technological change (related to the organization of productive activities). It concludes that investment-specific technological improvements have contributed significantly to long-term growth in Chile, in line with trends observed in other net commodity exporters, while neutral technological change has been slow.